Effect of different warm up protocols (deep feelings ,massage ,dynamic traction) on different levels of blood lactate and anaerobic power of athlete students - Sajedi, Heidar; Bas, Mustafa; Aydin, Elif (Progress in Nutrition, 2021)
The aim of this study is to investigate the effect of different warm up protocols (deep feelings ,massage ,dynamic traction) on different levels of blood lactate and anaerobic power of athlete students. The present study was quasi-experimental with pre and post -test design and a control group and also three experimental groups. After announcing ,36 students who have had at least three years of professional sports experience were chosen among qualified students and they were set randomly in four groups of deep feelings ,massage ,dynamic traction and control. Wingate test was used to measure anaerobic power .The test was performed by the 894E Monark Ergomedic as a Wingate test.The blood lactate of the participants of each group were measured in separate sessions using the German Scott Lactometer(using hand blood sample).Two methods of petrissage and Topotament were used in the massage group. In the deep feelings group ,the 11+ protocol designed by FIFA to improve performance and prevent player injury was used to warm up and five main muscle (Quadricepts femoris muscle ,Hamstring ,Hip flexor muscle , Hip Extensor muscle ,Ankle Extensor)were stretched. The results show that there was a significant difference between the results of anaerobic power test and blood lactate in those four groups. Based on the Tuki test and attention to the mean of post- test records compared to the pre –test, the two groups of dynamic traction and deep feelings compared to the control group had significantly better performance in anaerobic power and blood lactate(P<0/05) and there was no significant difference in the massage group compared to the control group(P>0/05). As a result, it can be said that all three methods of warming up including dynamic traction ,massage ,deep feelings improve the performance of the participants in the anaerobic power and blood lactate test compared to the control group and the performance of the students of deep feelings and dynamic traction group in terms of anaerobic power and blood lactate is better than massage group.